Peranan Regulasi Diri Terhadap Stres Akademik Santri Tahfidz Al-Qur’an - Fauzul Adim Ubaidillah; Nur Hasan; Muhammad Ghiyats Rasyid (Jurnal Multidisiplin Ibrahimy, 2025)
Self-regulation is an individual's skill in regulating emotions, behaviors, and thoughts to achieve long-term goals. Self-regulation is an essential skill in an educational context, as it can affect how students cope with the academic challenges and stress they face. This study aims to examine the relationship between self-regulation and academic stress of Tahfidz Al Qur'an students. This study used quantitative methods with a correlational design. The participants of this study amounted to 124 students of Tahfidz Al Qur'an obtained through convenience sampling technique. The data analysis of this study used a simple linear regression test. The results showed a negative correlation between self-regulation and academic stress (β = -0.161; p < 0.01) of students of Tahfidz Al Qur'an. Self-regulation can be an internal resource that Tahfidz students can develop to help them face various academic demands and reduce the impact of stress due to educational needs.